Proyecto De Factibilidad Para La Creación De Una Empresa Productora Y Comercializadora De Dispensadores Electrónicos Para Transformar Residuos De Jabón A Jabón Líquido En La Ciudad De Loja - Cabrera Ordoñez, Andrés Mauricio (2016)
Given the constant needs that exist throughout society, we saw a chance to grab one of them, with the creation of a producer and marketer of electronic dispensers for recycling soap to liquid soap company. Objectives was raised, who helped guide as a base and to implement the project in the first instance. We conducted a feasibility project for the creation of a producer and marketer of electronic dispensers for recycling soap to liquid soap in the city of Loja company. A market study to determine demand that these dispensers may have as well as the demands and preferences of consumers was conducted. We developed a management study to determine infrastructure needs for the normal conduct of business in different areas of the company. We conducted a study to determine the technical and productive capacity that will be developed using the technology and skilled labor. Were evaluated by a study with the respective financial indicators to estimate the overheads incurred in the creation of the company. This new proposal will help the family economy through full use of soap, building waste and discarded, while helping to avoid contamination. To determine the feasibility of the project the relevant market study was conducted with the application of 397 surveys representing sample of the population determine the values of total real and effective demand , thereby establishing that there is an effective demand of 14321 units of product to implement the production plant in the city. Supply analysis was also performed stating that competition would become producers of dispensers for liquid soap, obtaining an unmet 13984 units. Then, in the technical study, we determined the installed 4997 with a value of units in order to determine the capacity to be used by the company in the first year will be 53% capacity. In this study, macro and micro localization established , taking into consideration the physical, climatic, basic services; project engineering Universidad Nacional de Loja 5 and requirements of machinery, equipment , facilities and physical space to operate the company. The organizational structure that will have the company, will be a good development of the same, while the description of the functions that facilitate meeting the objectives. Then presents in detail the investment needed to start the business, within which the financial evaluation is established in order to establish the feasibility of the project, with the respective financial indicators, determining a net present value of 115850.85 a Rate internal Return of 53.83%, Benefit Cost Ratio of 1.88, the capital Recovery Period in 3 years. Sensitivity Analysis with an increase of 18 % and a decrease of -10%. Finally the conclusions and recommendations have taken into account as a key element to facilitate or improve corporate governance.